2018
DOI: 10.4114/intartif.vol21iss61pp95-110
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning-Based Analysis of the Association Between Online Texts and Stock Price Movements

Abstract: The paper presents the result of experiments that were designed with the goal of revealing the association between texts published in online environments (Yahoo! Finance, Facebook, and Twitter) and changes in stock prices of the corresponding companies at a micro level. The association between lexicon detected sentiment and stock price movements was not confirmed. It was, however, possible to reveal and quantify such association with the application of machine learning-based classification. From the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…However, focusing simply on the sentiment (positive and negative) dimensions does not always bring useful predictions (Li et al, 2014). In our previous research (Dařena et al, 2018), we revealed that it was possible to uncover and quantify a relationship between unstructured texts and stock price movements at a micro level with the application of machine learning. The data to be classified included the texts converted to their structured representation (bag-of-words).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…However, focusing simply on the sentiment (positive and negative) dimensions does not always bring useful predictions (Li et al, 2014). In our previous research (Dařena et al, 2018), we revealed that it was possible to uncover and quantify a relationship between unstructured texts and stock price movements at a micro level with the application of machine learning. The data to be classified included the texts converted to their structured representation (bag-of-words).…”
Section: Introductionmentioning
confidence: 95%
“…Moving averages based on a larger number of days (20 days) had more positive impact than moving averages based on a smaller number of days. The difference between the Simple Moving Average and the Exponentially Weighted Moving Average (NIST / SEMATECH, 2016) were negligible (Dařena et al, 2018).…”
Section: Processing Stock Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2014) used a minimal change of 1 % and Mittermayer (2004) worked with 1 % average change and 3 % extremes in the change. And last but not least, Darena et al (2018) used values 1 to 5 %. Regarding the window sizes it was more of a guess because there is no recommendation.…”
Section: Creating Time Windowsmentioning
confidence: 99%
“…Texts contain objective or subjective information (Darena et al, 2018). Behavioural finance theory says that emotions may deeply influence behaviour and decision making of individuals as well as whole human societies (Kearney, 2014).…”
Section: Introductionmentioning
confidence: 99%